Pharmacological treatment of recurrent idiopathic anterior uveitis - Szaflik, Jerzy; Bachta, Artur; Kulig, Maciej; Tłustochowicz, Mateusz; Stankiewicz, Andrzej; Tłustochowicz, Witold (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Recurrent anterior uveitis (AU) is an autoimmune disease that in 20% of patients leads to severe visual loss or blindness, thereby a severe disability and significant quality of life impairment. That is why, it is important to conduct a long term treatment after an acute phase of the disease, to keep the remission as long as possible. Up to 50% of patients with recurrent AU have no additional symptoms of systemic disease. This situation, classified as idiopathic AU (IAU), causes a lot of problems when a therapeutic strategy has to be chosen. Nevertheless, IAU is considered to be a first symptom of spondylarthropathy (SpA), even several dozen years prior to other typical manifestations of SpA. There have been published few papers concerning only small groups of patients with IAU, treated with disease modifying anti-rheumatic drugs. The authors present the recommendations for systemic treatment of IAU, based on their own clinical experience, and systematic review of the literature.